2005
DOI: 10.1080/13504850500068194
|View full text |Cite
|
Sign up to set email alerts
|

Export-led growth in Bangladesh: a time series analysis

Abstract: This paper examines time series evidence to investigate the link between exports and economic growth in Bangladesh. Using quarterly data for a period from 1976 to 2003 the paper finds that industrial production and exports are cointegrated. The results of an Error Correction Model (ECM) suggest that there is a long-run unidirectional causality from exports to growth in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 9 publications
10
62
1
Order By: Relevance
“…Thus, the authors summarized that a viable industrial sector was necessary to drive Bangladesh external trade. Mamun and Nath (2005) had showed that though industrial production and export were co-integrated at the long run, there exists a uni-directional causality running from export to economic growth in Bangladesh. Kemal et al (2002) also found a positive association between export growth, industrial production and economic growth for India as well as other South Asian economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the authors summarized that a viable industrial sector was necessary to drive Bangladesh external trade. Mamun and Nath (2005) had showed that though industrial production and export were co-integrated at the long run, there exists a uni-directional causality running from export to economic growth in Bangladesh. Kemal et al (2002) also found a positive association between export growth, industrial production and economic growth for India as well as other South Asian economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, exportled growth also improves the efficiency of the factors of production due to gains obtained from the economies of scale, by capturing a larger foreign market [Makki and Somawaru, 2004]. Bangladesh experienced a long run unidirectional causality from exports to economic growth [Mamun and Nath, 2005]. However, Love and Chandra [2005] reported both short run and long run unidirectional causality from income to exports in Bangladesh.…”
Section: Total Exports and Economic Growthmentioning
confidence: 99%
“…Empirical studies that are consistent with the ELG view include those undertaken by Rangasamy (2009), Jaunky (2011), Konya (2006, Awokuse (2007), Pradhan (2010), Aditya andAcharyya (2011), Parida andSahoo (2007), Siliverstovs and Herzer (2006), Al Mamun and Nath (2005), and Yoo (2008), amongst others. Rangasamy (2009) revealed a uni-directional causality running from exports to real GDP in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Keong et al (2005), the bounds testing approach discovered that exports stimulated positive economic growth in Malaysian economy both in the short and long run. Al Mamun and Nath (2005) also discovered that both industrial production and exports were co-integrated in Bangladesh with a distinct long run unidirectional causality running from exports to economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%